2013
DOI: 10.1515/hf-2013-0134
|View full text |Cite
|
Sign up to set email alerts
|

Pulp delignification with oxygen and copper(II)-polyimine complexes

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In one study, Korpi et al screened 189 different metal–ligand combinations for the oxidation of veratryl alcohol to veratraldehyde and found that copper complexes of 2,2′-bipyridine and 1,10-phenanthroline were especially active [ 30 , 31 ]. These complexes were also reported to be effective delignification catalysts when H 2 O 2 [ 32 ], O 2 [ 33 , 34 ], or both [ 35 ] were used as the oxidant. All approaches exhibited concurrent cellulose depolymerization that, although detrimental in instances where the cellulose is to be utilized in materials applications in which fiber strength is a crucial property, may prove beneficial if the desired product is monomeric sugars.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, Korpi et al screened 189 different metal–ligand combinations for the oxidation of veratryl alcohol to veratraldehyde and found that copper complexes of 2,2′-bipyridine and 1,10-phenanthroline were especially active [ 30 , 31 ]. These complexes were also reported to be effective delignification catalysts when H 2 O 2 [ 32 ], O 2 [ 33 , 34 ], or both [ 35 ] were used as the oxidant. All approaches exhibited concurrent cellulose depolymerization that, although detrimental in instances where the cellulose is to be utilized in materials applications in which fiber strength is a crucial property, may prove beneficial if the desired product is monomeric sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, integrating the published data on lignin removal and monomeric sugar yields during Cu-AHP pretreatment employing different H 2 O 2 loadings [0, 2, 4, and 6% (w/w)] with the results obtained in this study (Figures and ) indicates a synergistic effect of using both O 2 and H 2 O 2 as co-oxidants during the Cu-catalyzed alkaline–oxidative pretreatment of lignocellulosic biomass. Although there is literature precedence for enhancing O 2 -dependent delignification of pulp by the addition of H 2 O 2 or CuSO 4 , , to our knowledge, there are no published reports describing the simultaneous use of O 2 and H 2 O 2 as co-oxidants during the oxidative pretreatment of lignocellulosic biomass to recover both lignin and monomeric C-5 and C-6 sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular oxygen is a highly appealing oxidant that is widely utilized in the pulp and paper industry as a delignification and bleaching agent . During O 2 delignification of pulp, the free phenolic hydroxyl groups in lignin are ionized by the addition of alkali to generate phenolate ions, which are thought to initiate reactions with O 2 and result in the oxidation and solubilization of lignin into the liquid phase. During this process, the addition of catalysts such as copper sulfate in the presence or absence of nitrogen-based ligands could further activate oxygen and promote the delignification performance. Because H 2 O 2 is generally more reactive than O 2 and can generate hydroperoxide anions that oxidize carbonyl groups and cleave lignin aromatic rings, , H 2 O 2 has been utilized to improve the delignification performance of O 2 in pulp bleaching. , Therefore, employing both H 2 O 2 and O 2 as co-oxidants has the potential to improve delignification and the oxidation efficacy of the Cu-AHP pretreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation